Effect of Plyometric Training on Blood Pressure of University Athletes - Uzor, Theresa Nkiru; Uwa, Anthonia Chinyere; Ikwuka, David Chibuike (Athena: Physical Education and Sports Journal, 2024)
The study examined the effectiveness of plyometric training on university athletes’ blood pressure. Six plyometric training exercises were used for the study. Ankle hops, squat jumps and tuck jumps were chosen for lower body plyomeric training while push-ups, medicine ball-chest throws and side throws were used for upper body plyometric training with moderate intensity. The quasi-experimental research design was adopted for the study. 30 male athletes who voluntarily participated in the study were purposively selected and drawn from university male athletes body mass index (BMI) within the range of underweight to normal weight (≤18.5±24.9) (height, x=1.50±1.17cm; body weight, x=50.31±70.15kg), all athletes whose age-range fall between 18 and 25 years old. The general data were collated and analysed. Mean and standard deviation were used to describe the data collected for the study, Analysis of co-variance (ANCOVA) were used to test the hypotheses. The results revealed that athletes who were trained using LBPT and UBPT had reduced HR, SBP, and DBP better than those in the control group. These positive effects on blood pressure no doubt help in reducing the risk of cardiovascular diseases and promote good healthy lifestyle. Based on the findings, recommendations and conclusions were made.